2022
DOI: 10.1108/ejm-06-2021-0447
|View full text |Cite
|
Sign up to set email alerts
|

50 years of social marketing: seeding solutions for the future

Abstract: Purpose The purpose of this paper is synthesise social marketing literature over the past fifty years and deliver a set of guiding tenets to propel social marketing’s agenda forward. Design/methodology/approach Across three strands, this paper amalgamates theoretical and practitioner evidence from social marketing. This synthesis commences with a review, summary and critical discussion of five decades of social marketing research. Across Strands 2 and 3, the authors review 412 social marketing interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 105 publications
0
25
0
Order By: Relevance
“…Segmentation has been recognised as important to help social marketers better understand people, so that they can design social change programs to better meet the needs of more people (French, 2017). However, reviews of social marketing research and practice have shown that segmentation is one of the least used principles (Dietrich et al, 2022; Kubacki et al, 2017). It has also been noted that segmentation in social marketing is overly reliant on simple demographic or geographic variables (Dibb, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Segmentation has been recognised as important to help social marketers better understand people, so that they can design social change programs to better meet the needs of more people (French, 2017). However, reviews of social marketing research and practice have shown that segmentation is one of the least used principles (Dietrich et al, 2022; Kubacki et al, 2017). It has also been noted that segmentation in social marketing is overly reliant on simple demographic or geographic variables (Dibb, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, reviews of social marketing research and practice have shown that segmentation is one of the least used principles (Dietrich et al, 2022;Kubacki et al, 2017). It has also been noted that segmentation in social marketing is overly reliant on simple demographic or geographic variables (Dibb, 2017).…”
Section: A Short Form Segmentation Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…This section will form a case to respond to the question, 'What is social marketing?' The literature on it clearly indicates that social marketing as a theoretical term is debatable (Akbar et al, 2022 andDietrich et al, 2022). Alves (2010) emphasises that clarity is limited about social marketing, that causes misperception among researchers and scholars.…”
Section: Social Marketingmentioning
confidence: 99%
“…Over the years, research has been carried out to examine the effectiveness of social marketing (Dietrich et al, 2022;Wettstein & Suggs, 2016;Truong, 2014;Helmig & Thaler, 2010;Stead et al, 2007;Gordon et al, 2006). The review by Stead et al (2007) suggests that there is evidence of social marketing effectiveness when the aim is to achieve change at an individual level (downstream), but the effectiveness is limited when it comes to policy or environmental change (upstream).…”
Section: Social Marketingmentioning
confidence: 99%